Use of fibrinolytics and deoxyribonuclease in adult patients with pleural empyema: a consensus statement. Issue 9 (September 2021) - Chaddha, Udit; Agrawal, Abhinav; Feller-Kopman, David; Kaul, Viren; Shojaee, Samira; Maldonado, Fabien; Ferguson, Mark K; Blyth, Kevin G; Grosu, Horiana B; Corcoran, John P; Sachdeva, Ashutosh; West, Alex; et al.
Summary: Although our understanding of the pathogenesis of empyema has grown tremendously over the past few decades, questions still remain on how to optimally manage this condition. It has been almost a decade since the publication of the MIST2 trial, but there is still an extensive debate on the appropriate use of intrapleural fibrinolytic and deoxyribonuclease therapy in patients with empyema. Given the scarcity of overall guidance on this subject, we convened an international group of 22 experts from 20 institutions across five countries with experience and expertise in managing adult patients with empyema. We did a literature and internet search for reports addressing 11 clinically relevant questions pertaining to the use of intrapleural fibrinolytic and deoxyribonuclease therapy in adult patients with bacterial empyema. This Position Paper, consisting of seven graded and four ungraded recommendations, was formulated by a systematic and rigorous process involving the evaluation of published evidence, augmented with provider experience when necessary. Panel members participated in the development of the final recommendations using the modified Delphi technique. Our Position Paper aims to address the existing gap in knowledge and to provide consensus-based recommendations to offer guidance in clinical decision making when considering the use of intrapleural therapy in adult patients with bacterial empyema.